RELATIONSHIP OF ADAMTS WITH BIOCHEMICAL PARAMETERS IN METABOLIC SYNDROME - Semiramis Doğan Zeybek; Adnan Adil Hişmioğulları (Sabiad)
Objective: The aim of our study was to investigate the potential of a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) proteins, which are thought to change in levels as a result of the deterioration of the extracellular matrix in the vessels due to the development of atherosclerosis, to be used as biochemical markers in individuals with metabolic syndrome and diabetes. Material and Methods: Our study was carried out with the participation of 10 female individuals diagnosed with diabetes in the experimental group, 10 female individuals diagnosed with metabolic syndrome and 11 healthy female individuals the aged 25-65 years. Biochemical analyses and anthropometric measurements were performed and blood samples were taken. Serum was separated from the blood samples. ADAMTS-1 and ADAMTS-9 serum levels were analysed using ELISA method. Results: When the amount of ADAMTS-1 protein was analysed, ADAMTS-1 level was found to be statistically (p<0.01) significantly lower when the experimental and control groups were compared. When the amount of ADAMTS-9 protein was analysed, similarly statistically significant (p<0.01) decreases were found between the groups. Conclusion: This is a preliminary study showing that ADAMTS-1 and ADAMTS-9 proteins can be used in the early diagnosis and treatment of metabolic syndrome and in the pathogenesis of the disease. However, this potential needs to be investigated in detail.